Conductivity study on plasticized chitosan acetate based electrolytes doped with silver triflate salt system / A.M.M. Ali ... [et al.] - Ali, A.M.M.; Yahya, M.Z.A.; Harun, M.K.; Mohamad, A.A. (Faculty of Applied Sciences, 2005)
Plasticized polymer electrolytes composed of chitosan as the host polymer, ethylene carbonate (EC) as the plasticizer and silver triflate (AgCFjiSOj) as the doping salt were prepared by the solution cast technique. These complexes with different amounts of salts and plasticizers were investigated as possible ionic conducting polymers. This salt was chosen based on the ability of silver cation to exist as monovalent cation, which could influence the mobility of the ions in the chitosan-based electrolytes. The highest electrical conductivity, a for the chitosan-silver triflate salt at room temperature was 1.0 x 10' S cm'1. Conductivity for the plasticized AgCFjSOs (Ag Tf) doped chitosan polymer was also studied as a function of temperature between 300 K and 363 K. The plot ofln(dT) versus lCf/T for each sample obeys Arrhenius rule indicating the conductivity to be thermally assisted. The activation energy, Ea was calculated from the Arrhenius plots and the increase in conductivity can be explained in terms of the decrease in Ea and vice versa. The highest conducting CA-EC-AgCF3SOs complex has the lowest Ea of 0.60 eV. FTIR spectroscopy and XRD techniques were carried out for the complexation studies.